Strengthening Maritime Governance as an Effort to Accelerate the Development in Lingga Regency - Ade Masniary; Aditya Indrawan (Journal Governance Bureaucratic Review, 2026)
ABSTRACT   This study examines the strengthening of maritime governance in Lingga Regency as a strategic effort to accelerate the development of disadvantaged areas through the principles of good governance and the blue economy. As an archipelagic region where nearly 90 per cent of the territory consists of marine areas, Lingga Regency faces persistent challenges related to the distribution of authority, limited fiscal capacity, and the performance of local governance institutions. Using a descriptive qualitative approach based on an extensive review of relevant literature, this study focuses on three key dimensions: the institutional framework of maritime governance, the development of fisheries-based maritime economic activities within the blue economy paradigm, and the integration of marine resource conservation with coastal social equity. The findings reveal that effective maritime governance in Lingga Regency depends largely on strong coordination among national, provincial, and district governments through a multi-level governance mechanism, supported by meaningful participation of coastal communities, particularly the Suku Laut (Sea Tribe). The implementation of initiatives such as the Modern Fishermen Village (Kalamo), fisher social protection programs, and the designation of Regional Marine Conservation Areas (KKPD) has contributed to a more inclusive and sustainable maritime development trajectory. Overall, the study concludes that collaborative and integrated maritime governance is a critical foundation for achieving economic resilience and environmental sustainability in archipelagic regions.